KONTRIBUSI SAID NURSI TERHADAP PERUBAHAN SEKULARISME DI TURKI - Ismail, Muhammad Syakir (FITRAH: International Islamic Education Journal, 2023)
Said Nursi is a Muslim figure who has contributed to changes in secularism in Turkey. Turkey was originally based on the Koran and Sunnah, becoming a republic based on secularism in all aspects of life under Attaturk's rule. However, Turkey now looks different, where secularism is fading and people can carry out activities in accordance with the Qor’an and Sunnah. This was caused by the thoughts born by Said Nursi which brought changes to secularism in Turkey. This research aims to describe Said Nursi's contribution to changes in secularism in Turkey whose study focuses on Darul Hikmetil Islamiye, Sufism Amali, and Risala An-Nur. This research is a literature review (character study) with a descriptive qualitative approach. The subject data comes from books, articles and historical notes about Said Nursi's thoughts which are used as objects of study. The data was analyzed descriptively in collaboration with content analysis. So the results of the research state that Darul Hikmetil Islamiye, Sufism Amali, and Risale An-Nur which were pioneered by Said Nursi not only changed aspects of Turkish society in their time in maintaining Turkey as a secular Islamic country, even though this movement was very small in scope at that time. However, Nursi has given birth to new cadres so that today not only in Turkey, even in all corners of the world they can apply his thoughts in the lives of Islamic communities.